Improving Patients’ and Families’ Knowledge of Psychosocial Hazards through Education at Manar Medika Clinic - Febriani, Nelly; Fadhilah, Nur Syafrina; Amma, Salsabila Shafa Muradi; Hidayat, Wahid; Afiati, Farida; Humaira, Khansa; N, Nurlaila; Roselowati, Yessy Rahma; A, Atikah; Putri, Nafisya Nur Adiba Purnomo; Hartati, Julia (Yayasan Daarul Huda Kruengmane, 2025)
Psychosocial hazards are a significant challenge in primary healthcare services because they can affect the mental well-being of patients and their families. Emotional strain resulting from chronic illness, treatment uncertainty, and changes in family roles often leads to stress, anxiety, and emotional exhaustion. A lack of understanding regarding psychosocial factors frequently results in delayed mental health management, ultimately impacting patients’ quality of life. This community service activity aimed to enhance patients’ and families’ knowledge of psychosocial hazards through participatory education conducted at Manar Medika Clinic, Depok. The method used was a quantitative approach with a cross-sectional design. Education was delivered through interactive lectures, group discussions, and demonstrations involving ten respondents selected through total sampling. Evaluation was conducted by measuring knowledge levels before and after the activity using a structured questionnaire to assess knowledge improvement following the intervention. The results showed a significant increase in knowledge. The participants’ average score rose from 46 to 98, with a 52-point difference. Before the educational session, most respondents had low knowledge levels (70%); however, after the intervention, all participants (100%) reached the “good” category. These findings indicate that the educational activity was effective in improving participants’ understanding of psychosocial hazards, raising awareness of the importance of emotional support, and helping patients and families manage stress more adaptively.